2018
DOI: 10.1021/acs.est.8b01435
|View full text |Cite
|
Sign up to set email alerts
|

New Perspectives on CO2, Temperature, and Light Effects on BVOC Emissions Using Online Measurements by PTR-MS and Cavity Ring-Down Spectroscopy

Abstract: Volatile organic compounds (VOC) play important roles in atmospheric chemistry, plant ecology, and physiology, and biogenic VOC (BVOC) emitted by plants is the largest VOC source. Our knowledge about how environmental drivers (e.g., carbon, light, and temperature) may regulate BVOC emissions is limited because they are often not controlled. We combined a greenhouse facility to manipulate atmospheric CO2 ([CO2]) with proton-transfer-reaction mass spectrometry (PTR-MS) and cavity ring-down spectroscopy to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 63 publications
1
24
1
Order By: Relevance
“…Our experiment was conducted in August. Exposing Picea abies to a low atmospheric CO 2 concentration (50 ppm) also did not change the amount of monoterpenes stored in current year needles ( Huang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 96%
“…Our experiment was conducted in August. Exposing Picea abies to a low atmospheric CO 2 concentration (50 ppm) also did not change the amount of monoterpenes stored in current year needles ( Huang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 96%
“…This is helpful as A net is a good proxy for the rate of photosynthesis and a recent 13 C-pulsed labeling study has shown that newly assimilated carbon can be emitted as monoterpenes within 1 h (Huang et al, 2018). Further, depending on whether the tree's growth is in the reproductive or vegetative phase (Huijser and Schmid, 2011), the assimilated carbon can be allocated differently, impacting the emitted BVOC flux. For example, one could expect that in the constitutive growth phase, emissions of BVOCs would be lower, whereas, in the reproductive phase, when flowering and fruiting occur, due to the important functional roles BVOCs play in attracting pollinators and for plant defense, there would be increased emissions of BVOCs (Peñuelas, 2003).…”
Section: Emission Of Bvocs From Mahogany Including Lightmentioning
confidence: 99%
“…We have demonstrated that flame sterilization of culture medium vessel openings can result in a significant decline in the pH of freshwater media due to the dissolution and hydration of CO 2 . This decline in pH has several implications, as optimal pH ranges for algal photosynthesis and growth are often narrow and well defined (Huang et al 2018). Moreover, under current climate scenarios, research into the effects of small pH shifts is common yet could be compromised by this observation.…”
Section: Comments and Recommendationsmentioning
confidence: 99%